Chloroquine and hydroxychloroquine-related ocular adverse events in SLE treatment: a real-world disproportionality analysis based on FDA adverse event reporting system (FAERS) - Li, Xiang; Zhang, Si-Qi; Wang, Ke-Rui; Wu, Shi-Nan; Wang, Meng-Yuan; Chen, Cui-Ting; Dong, Nuo (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to evaluate the risk of adverse events associated with chloroquine (CQ) and hydroxychloroquine (HCQ) in patients with systemic lupus erythematosus (SLE), using data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsDisproportionality analysis was conducted using the Reporting Odds Ratio (ROR) to detect potential safety signals. Sensitivity analyses were performed to validate these signals, and the time to onset for each Preferred Term (PT) was assessed.ResultsBetween 2004 and 2024, a total of 2,575 adverse event reports related to HCQ or CQ use in patients with SLE were identified in the FAERS database, of which 437 involved ocular adverse events. The most frequently reported ocular conditions were cataract, macular degeneration, and glaucoma. Disproportionality analysis demonstrated strong associations between HCQ/CQ use and retinal degeneration (ROR = 28.5, 95%CI: 19.94–40.74), cystoid macular oedema (ROR = 12.46, 95%CI: 8.01–19.37), and optic atrophy (ROR = 6.55, 95%CI: 3.51–12.19). Sensitivity analyses, conducted after excluding SLE cases, indicated that all but one event (vitreous floaters) remained statistically significant, suggesting that these risks are more likely attributable to HCQ/CQ exposure than to the underlying disease. The time-to-onset analysis showed that cataract had the shortest average onset time (125.5 days), whereas retinal degeneration had the longest (937.5 days).ConclusionThe extensive clinical use of HCQ and CQ raises significant concerns regarding their ocular safety profile. This study provides real-world pharmacovigilance evidence supporting a substantial risk of ocular adverse events associated with HCQ/CQ use. Further mechanistic and prospective studies are warranted to elucidate the underlying pathophysiological pathways and to confirm these associations.